2016
DOI: 10.1111/boc.201500056
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic amounts of cisplatin induce either checkpoint adaptation or apoptosis in a concentration‐dependent manner in cancer cells

Abstract: Checkpoint adaptation might be a common biochemical pathway taken by human cancer cells in response to pharmacologically relevant, cytotoxic amounts of damaged DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 45 publications
4
22
0
Order By: Relevance
“…In accordance with these results, it was reported that cisplatin can induce either apoptosis or necrosis depending on the dose [20] and the metabolic and energy status of the cells [21].…”
Section: Untreated Hela Cells Had Intact Plasma Membranes and Numerousupporting
confidence: 74%
“…In accordance with these results, it was reported that cisplatin can induce either apoptosis or necrosis depending on the dose [20] and the metabolic and energy status of the cells [21].…”
Section: Untreated Hela Cells Had Intact Plasma Membranes and Numerousupporting
confidence: 74%
“…12 By contrast if the concentration of cisplatin applied to cells was at supra-pharmacological levels (100-300 mM), cells died within 48 h and do not undergo checkpoint adaptation. 10 …”
Section: Discussionmentioning
confidence: 99%
“…Although it was believed that cells would die by apoptosis when challenged by damaged DNA, cells have the possibility to engage another pathway known as checkpoint adaptation. 10 During checkpoint adaptation, cells enter mitosis despite having damaged DNA. 11,12 In these cells, the activity of Chk1 decreases, thus permitting the activation of Cdk1 followed by entry into mitosis damaged DNA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, checkpoint adaptation has been documented in both uni-and multicellular systems including budding yeast, Xenopus egg extracts, plant and cancer cells (Carballo et al, 2006;Kubara et al, 2012;Sandell and Zakian, 1993;Swift and Golsteyn, 2016;Syljuasen et al, 2006;Toczyski et al, 1997;Yoo et al, 2004). One striking similarity in the process of checkpoint adaptation across all organisms is the critical contribution of PLK1 (Liang et al, 2014) and its homologues such as budding yeast Cdc5 (Syljuasen et al, 2006;Toczyski et al, 1997).…”
Section: Introductionmentioning
confidence: 99%